1999
DOI: 10.1136/bmj.318.7198.1585
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of hospital care and treatment seeking for pain from sickle cell disease: qualitative study

Abstract: Objective To investigate how sociocultural factors influence management of pain from sickle cell disease by comparing the experiences of those who usually manage their pain at home with those who are more frequently admitted to hospital for management of their pain. Design Qualitative analysis of semistructured individual interviews and focus group discussions. Participants 57 participants with genotype SS or S/ -thal (44 subjects) or SC (9) (4 were unknown). 40 participants took part in focus groups, six took… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
138
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 21 publications
3
138
1
Order By: Relevance
“…Patients with SCD may experience problematic interpersonal experiences in the healthcare setting. 8,9 In previous work, we have shown that hospitalized SCD patients are more likely than other hospitalized patients to report poor interpersonal experiences of care. 10 Negative healthcare provider attitudes serve as a barrier to the delivery of appropriate pain management among these patients, and poor communication with healthcare providers is associated with lower trust and problematic clinical outcomes, such as discharge against medical advice.…”
Section: Introductionmentioning
confidence: 93%
“…Patients with SCD may experience problematic interpersonal experiences in the healthcare setting. 8,9 In previous work, we have shown that hospitalized SCD patients are more likely than other hospitalized patients to report poor interpersonal experiences of care. 10 Negative healthcare provider attitudes serve as a barrier to the delivery of appropriate pain management among these patients, and poor communication with healthcare providers is associated with lower trust and problematic clinical outcomes, such as discharge against medical advice.…”
Section: Introductionmentioning
confidence: 93%
“…Providing care to patients with frequent ED visits can contribute to frustration levels experienced by both patients and ED staff. [10][11][12][13] It is a common perception of emergency physicians and staff that SCD patients presenting to the ED are opioid dependent, and this belief may lead to inconsistent or inadequate treatment. 14,15 Both physicians and nurses tend to overestimate the prevalence of addiction in the SCD population, which has been documented to range from 0% to 11%.…”
Section: Discussionmentioning
confidence: 99%
“…Control may have a positive influence on these factors [22]. This factor may be particularly important for patients with SCD and may be a possible explanation for the fact that no difference in pain or quality of life was found between the CIgroup and PCA-group despite the large difference in the amount of morphine used [23,24]. Furthermore, patients in the PCA-group appeared to accept a pain score of 5.5 and did not titrate to achieve a pain-free state, while most health professionals titrate pain medication to reduce even mild pain.…”
Section: Side Effects and Adverse Eventsmentioning
confidence: 99%